2021
DOI: 10.1002/jez.b.23066
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic bases of a polyphenism

Abstract: Polyphenism—in which multiple distinct phenotypes are produced from a single genotype owing to differing environmental conditions—is commonplace, but its molecular bases are poorly understood. Here, we examine the transcriptomic bases of a polyphenism in Mexican spadefoot toads (Spea multiplicata). Depending on their environment, their tadpoles develop into either a default “omnivore” morph or a novel “carnivore” morph. We compared patterns of gene expression among sibships that exhibited high versus low produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 79 publications
(103 reference statements)
2
11
0
Order By: Relevance
“…Our study thereby provides a window into the developmental origins of a novel phenotype and the early stages of PLE. This study also complements recent work on this system [3436] regarding how gene expression changes undergird phenotypic plasticity and the evolution of the distinctive carnivore phenotype.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our study thereby provides a window into the developmental origins of a novel phenotype and the early stages of PLE. This study also complements recent work on this system [3436] regarding how gene expression changes undergird phenotypic plasticity and the evolution of the distinctive carnivore phenotype.…”
Section: Introductionsupporting
confidence: 78%
“…[63,64]). Moreover, recent studies have shown that plasticity in spadefoots may often entail regulating oxidative stress [34,65]. Thus, phenotypic accommodation to a new environment in the brain may involve energetic changes that can affect cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the loss of cues or insufficient levels or duration of cues can result in “intermediate” and mosaic phenotypes. However, a recent study suggests that cholesterol biosynthesis and peroxisome activity might be important regulators of the morph transition because of their system-wide effects on metabolism and hormone production, suggesting a role for a top-down, “master regulator” model (Levis et al, 2021 ). In addition, whether the component traits of the carnivore morph are activated sequentially—thus making the architecture actually more akin to that of ganged switches—and are responding to the same internal (e.g., hormonal) signals, as opposed to environmental cues, requires further study.…”
Section: Evolution and Mechanisms Of Developmental Switchesmentioning
confidence: 99%